Autopsy findings of acute erythroid leukemia - Mayur Parkhi; Nabhajit Mallik; Deepesh Lad; Man Updesh Singh Sachdeva; Amanjit Bal; Pankaj Malhotra; Suvradeep Mitra (Autopsy and Case Reports, 2023)
Acute erythroid leukemia (AEL) is an exceedingly uncommon but distinct hematological malignancy that shows neoplastic proliferation of erythroid precursors with maturation arrest and no significant myeloblasts. We describe an autopsy case of this rare entity in a 62-year-old man with co-morbidities. He underwent a bone marrow (BM) examination for pancytopenia during the first outpatient department visit, which revealed an increased number of erythroid precursors with dysmegakaryopoiesis suggesting the possibility of Myelodysplastic syndromes (MDS). Thereafter, his cytopenia got worsened, warranting blood and platelet transfusions. Four weeks later on the second BM examination, AEL was diagnosed based on morphology and immunophenotyping. Targeted resequencing for myeloid mutations revealed TP53 and DNMT3A mutations. He was initially managed along febrile neutropenia with the stepwise escalation of antibiotics. He developed hypoxia attributed to anemic heart failure. Subsequently, he had hypotension and respiratory fatigue pre-terminally and succumbed to his Illness. A complete autopsy showed infiltration of various organs by AEL and leukostasis. Besides, there was extramedullary hematopoiesis, arterionephrosclerosis, diabetic nephropathy (ISN-RPS class II), mixed dust pneumoconiosis, and pulmonary arteriopathy. The histomorphology of AEL was challenging, and the differential diagnoses were many. Thus, this case highlights the autopsy pathology of AEL, an uncommon entity with a strict definition, and its relevant differentials.